High-Throughput Chinmedomics Strategy Discovers the Quality Markers and Mechanisms of Wutou Decoction Therapeutic for Rheumatoid Arthritis - Li, Taiping; Wu, Fangfang; Zhang, Aihua; Dong, Hui; Ullah, Ihsan; Lin, Hao; Miao, Jianhua; Sun, Hui; Han, Ying; He, Yanmei; Wang, Xijun (Frontiers in Pharmacology, 2022)
Wutou decoction (WTD) is a common prescription treatment for rheumatoid arthritis (RA), but its quality control and quality markers (Q-markers) have not been thoroughly investigated. The metabolic mechanism of WTD treatment of RA rats was clarified using untargeted metabolomics, and the in vivo pharmacodynamic components of WTD were identified by serum pharmacochemistry of traditional Chinese medicine. The main components and Q-markers of WTD reversing abnormal metabolism were determined applying Pearson correlation analysis. WTD reduced the levels of tumor necrosis factor and interleukin 6 while inhibiting synovial tissue edema and inflammation in RA rats, according to X-ray and histological examination. Moreover, the serum contained 28 chemical components of the WTD, including 12 prototype components and 16 metabolites. Furthermore, WTD affected linoleic acid and arachidonic acid metabolism by reversing more than half of the biomarker levels (13/25), suggesting that this might be a key mechanism for WTD therapy of RA rats. Aconitine, L-ephedrine, L-methylephedrine, quercetin, albiflorin, paeoniflorigenone, astragaline A, astragaloside II, glycyrrhetic acid, glycyrrhizic acid, licurazide, and isoliquiritigenin were discovered as Q-markers of WTD in a Pearson correlation analysis between potential biomarkers and components absorbed. Finally, the Q-markers of WTD therapy in RA rats were extensively examined in this work.